Advantages of the association of resveratrol with oral contraceptives for management of endometriosis-related pain - Maia, Hugo (Dove Medical Press, 2012)
BACKGROUND: The effect of resveratrol on the management of endometriosis-related pain was investigated in 12 patients who failed to obtain pain relief during use of an oral contraceptive containing drospirenone + ethinylestradiol. METHODS AND RESULTS: The addition of 30 mg of resveratrol to the contraceptive regimen resulted in a significant reduction in pain scores, with 82% of patients reporting complete resolution of dysmenorrhea and pelvic pain after 2 months of use. In a separate experiment, aromatase and cyclo-oxygenase-2 expression were investigated in the endometrial tissue of 42 patients submitted to laparoscopy and hysteroscopy for the management of endometriosis. Sixteen of these patients were using oral contraceptives alone prior to hospital admission, while the remaining 26 were using them in combination with resveratrol. Inhibition of both aromatase and cyclo-oxygenase-2 expression was significantly greater in the eutopic endometrium of patients using combined drospirenone + resveratrol therapy compared with the endometrium of patients using oral contraceptives alone. CONCLUSION: These results suggest that resveratrol potentiates the effect of oral contraceptives in the management of endometriosis-associated dysmenorrhea by further decreasing aromatase and cyclo-oxygenase-2 expression in the endometrium.